ANALISIS PENAWARAN (LABOR SUPPLY) TENAGA KERJA PADA MASA PANDEMI COVID-19 DI PROVINSI RIAU TAHUN 2020-2021 - ,Lapeti Sari, Eko Susanto , Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The Covid-19 pandemic has greatly affected the community's economy and the sustainability of work. This study aims to analyze labor bidders during the Covid-19 pandemic in Riau Province in 2020-2021. This research uses quantitative research methods with descriptive analysis tools. The results of this study indicate that social restrictions on a regular basis resulted in a slowdown in the economy during the Covid-19 pandemic in Riau Province. The main factor that influences the high low supply of labor during the Covid-19 pandemic in terms of the labor force that works is the presence of added workers and labor shifting. While what affects the unemployment rate is the existence of: Business bankruptcy; Termination of employment, well as; The manpower was laid off. Keywords: Pandemic, Labor Supply